Bi-directional series-parallel elastic actuator and overlap of the actuation layers. (26th January 2016) - Furnémont, Raphaël; Mathijssen, Glenn; Verstraten, Tom; Lefeber, Dirk; Vanderborght, Bram
Abstract: Several robotics applications require high torque-to-weight ratio and energy efficient actuators. Progress in that direction was made by introducing compliant elements into the actuation. A large variety of actuators were developed such as series elastic actuators (SEAs), variable stiffness actuators and parallel elastic actuators (PEAs). SEAs can reduce the peak power while PEAs can reduce the torque requirement on the motor. Nonetheless, these actuators still cannot meet performances close to humans. To combine both advantages, the series parallel elastic actuator (SPEA) was developed. The principle is inspired from biological muscles. Muscles are composed of motor units, placed in parallel, which are variably recruited as the required effort increases. This biological principle is exploited in the SPEA, where springs (layers), placed in parallel, can be recruited one by one. This recruitment is performed by an intermittent mechanism. This paper presents the development of a SPEA using the MACCEPA principle with a self-closing mechanism. This actuator can deliver a bi-directional output torque, variable stiffness and reduced friction. The load on the motor can also be reduced, leading to a lower power consumption. The variable recruitment of the parallel springs can also be tuned in order to further decrease the consumption of the actuator for a given task. First, an explanation of the concept and a brief description of the prior work done will be given. Next, the design and the model of one of the layers will be presented. The working principle of the full actuator will then be given. At the end of this paper, experiments showing the electric consumption of the actuator will display the advantage of the SPEA over an equivalent stiff actuator.